RESEPSI EKSEGESIS UMAT ISLAM TERHADAP BUDAYA SEDEKAH (Studi Living Hadits di Masjid Sulthoni Wotgaleh, Sleman, Yogyakarta) - Muhammad Irsad (Lembaga penelitian dan pengabdian kepada Masyarakat, 2019)
This study aims to reveal one of the practices of alms culture at Sulthoni Wotgaleh Mosque, Sleman, Yogyakarta. Alms made in the form of money, building materials to food and beverages intended for congregation prayers Friday. This study seeks to trace the origins of the emergence of alms practices, and reveal the exegesis of Muslims to the hadith of the Prophet, which became the theological root of the emergence of the practice of alms. The results of this study concluded that; first, the origin of the alms practices that took place at Sulthoni Mosque was motivated by the initiative of Muslims who wanted to find an 'alternative way' of supporters for their wishes or wishes to come true. Secondly, there are three kinds of exegesis receptions for Muslims about giving charity, which is a form of gratitude, as a repellent, and as a means of facilitating rizki. Third, the alms that entrenched and the crowded of the Sulthoni mosque visited by pilgrims could not be separated by the sacred side of the tomb of Panembahan Purboyo I located in the mosque.